THE INFLUENCE OF DEMOGRAPHIC FACTORS ON BUSINESS SIMULATION EFFECTIVENESS - Mohd. Hizam Hanafiah; Md. Daud Ismail (Journal of ICT, 2006)
Educators, employers and policy makers have been searching for ways to help their student learn to think. In order to assist student to think and solve problems, business educators have turned to business simulation as an alternative way to develop people. Business simulation is a teaching method that can assist in developing a learning environment, which exposes students to complex situations that needs strategic decision- making. At Faculty of Economics and Business UKM, business simulation has been integrated in strategic management course as a platform for students to make management decision in a dynamic environment. A study on 165 students had been conducted to measure the influence of demographic factors on the effectiveness of business simulation. Our findings show that students’ gender, race, academic qualification, academic program and career ambition have influenced the simulation effectiveness. On the other hand, students’ C.G.P.A, simulation performance, English language capability and working experience have no influence on the effectiveness of business simulation.